Pelaksanaan Hak Mengajukan Rancangan Peraturan Daerah dan Hak Imunitas Anggota Dewan Perwakilan Rakyat Daerah - Mhd Ansori (Wajah Hukum, 2019)
There are several opinions regarding the function of the Regional People Representative Assembly, according to Jimly Asshiddiqie "the function of legislation or regulation in its concrete form is manifested in the function of forming regulations that bind citizens" and Bagir Manan said "the budget function is the right to participate in setting regional annual budgets". In practice, in formulating legislation including the formulation and formulation of regional regulations, Regional People Representative Assembly often has difficulties in generating initiatives to draft Regional Regulations that will become a policy in the administration of government and development. According to Bagir Manan in his book explaining the right of immunity namely the immunity rights of a member of the House of Representatives from certain legal processes, unless the immunity is dated or abandoned. To analyze how the application of the concept of the implementation of rights proposes a draft regional regulation and immunity rights for members of the Regional Representatives Council in Indonesia. the type of research used is normative juridical research, namely research focused on examining the application of rules or norms in positive law. This research uses "conceptual approaches, legislative approaches, and historical approaches".